Discovery of anticancer targets for triple-negative breast cancer through comparative analysis of gene dependency score - Kim, Bo Kyung; Kim, Gahee; Hur, Wonhee; Choi, Yoojin; Hwangbo, Suhyun; Ryu, Jae Yong (Biotechnology and bioprocess engineering, 2024)
Patients with triple-negative breast cancer (TNBC) often face an unfavorable prognosis due to the lack of targeted therapy. Thus, identifying drug targets specific to the TNBC subtype is crucial for effective treatment. Here, we propose a strategy to identify potential inhibitory targets specific to this subtype based on the gene dependency score (GDS), a quantitative measure of essentiality of each gene determined in cancer cell lines. Specifically, we compared the GDS values of 17,387 genes among cell lines of four breast cancer (BC) subtypes, namely luminal A, luminal B, HER2-positive, and TNBC, to identify genes showing specific essentiality in TNBC subtype cell lines. Twenty-two genes were predicted as potential inhibitory targets. Of these, we selected two genes, ILK and RHOA , based on survival analysis conducted across the four BC subtypes. We propose these two genes as potential biomarkers for TNBC. Furthermore, we experimentally validated that inhibiting ILK expression with a specific inhibitor reduced cell viability more in TNBC subtype cell lines than in other BC subtype cell lines. Therefore, ILK is a potential drug target specific to TNBC. The strategy proposed is expected to be useful in identifying biomarker and therapeutic target genes in not only BC but also other cancers.